Antimicrobial And Phytochemical Screening Of Rhizome Extracts Of Some Native Medicinal Plant Of Himachal Pradesh (India) (Applied Biological Research, 2013)
The ethanolic and aqueous extracts of rhizomes of five medicinal plants (Agave  sisaliana, Euphorbia royleana, Zantedeschia aetthiopica, Stephania glabra and  Mirabilis jalapa), collected from Solan district of Himachal Pradesh (India),  were assayed for antimicrobial activity against eight bacteria including some  human pathogens. The ethanolic and aqueous extracts of these plants were less  effective against Escherichia coli, Bacillus subtilis and Staphylococcus aureus whereas M. jalapa extract was ineffective against Shigella sp. The qualitative  phytochemical analysis confirmed the presence of various phytochemicals like  tannins, alkaloids, saponins, steroids, phenols and glycosides in the rhizome  extracts of these plants. The plant extracts tested possessed antimicrobial  potential. Further, the presence of phytochemicals such as tannins, alkaloids,  saponins, etc. in the rhizome extracts of these plants suggest their anticancer  potential.
Keywords: Antimicrobial activity aqueous extract; ethanolic extract; phytochemical; pathogens; rhizome